Socio-Environmental Crises and Cognitive Ageing. Exploring the Cognitive Impact of the COVID-19 Pandemic and Climate Crises on Older Adults' Memory and Verbal Fluency - Martina Brandt (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2025)
Socio-environmental crises such as the ones induced by the COVID-19 pandemic and ongoing climate change significantly impact individual health, not only but especially at older ages. While the health effects of COVID-19 lockdowns and the cardiovascular risks posed by climate change (especially heat waves) in the older population have been studied, their differential impacts on cognitive functioning in later life remain less understood, despite their relevance for the sociology of age(ing). This article thus explores the “cognitive impact” of socio-environmental crises by addressing two questions: (1)~How does cognitive functioning change from the prepandemic to the postlockdown phase, and how does this compare with baseline cognitive changes? (2)~How are average and peak summer temperatures linked to cognitive change over a~2-year period? Using longitudinal data from the Survey of Health, Ageing and Retirement in Europe (SHARE), we analysed cognitive changes in a~sample of adults aged~50+ in Germany from 2004 to 2022. Random effects change score analysis focused on two cognitive measures: memory and verbal fluency. Results show that COVID-19–related cognitive decline in memory is significantly greater than baseline change rates of cognitive decline, but no such effect was observed for verbal fluency. Higher average summer temperatures are associated with faster declines in memory and verbal fluency, while peak summer temperatures are not correlated with cognitive functioning. While the social and biological mechanisms behind such changes still need to be disentangled scientifically, the sociopolitical need for action during times of polycrises is unquestionable. – – Sozial-ökologische Krisen, wie sie durch die COVID-19-Pandemie sowie den fortschreitenden Klimawandel hervorgerufen werden, haben signifikante Auswirkungen auf die individuelle Gesundheit – nicht ausschließlich, aber insbesondere im höheren Lebensalter. Während die gesundheitlichen Folgen pandemiebedingter Lockdowns sowie die kardiovaskulären Risiken klimatischer Extremereignisse (insbesondere Hitzewellen) für ältere Bevölkerungsgruppen bereits empirisch untersucht wurden, ist über ihre differentiellen Effekte auf die kognitive Leistungsfähigkeit im höheren Lebensalter bislang wenig bekannt – obwohl diese für eine Soziologie des Alterns von zentraler Relevanz sind. Der Beitrag untersucht daher den ,,kognitiven Einfluss“ sozial-ökologischer Krisen und adressiert zwei Fragestellungen: (1) In welcher Weise verändert sich die kognitive Leistungsfähigkeit von der präpandemischen zur post-lockdown-Phase – und wie sind diese Veränderungen im Vergleich zu altersnormativen kognitiven Verläufen einzuordnen? (2) In welchem Zusammenhang stehen durchschnittliche oder maximale Sommertemperaturen mit kognitiven Veränderungen über einen Zeitraum von zwei Jahren? Anhand von Längsschnittdaten des Survey of Health, Ageing and Retirement in Europe (SHARE) werden kognitive Veränderungen bei in Deutschland lebenden Personen ab 50 Jahren im Zeitraum von 2004 bis 2022 untersucht. Um Change Scores in zwei kognitiven Indikatoren, Gedächtnisleistung und verbaler Funktion, zu untersuchen, werden Random-Effects-Modelle verwendet. Die Ergebnisse zeigen, dass pandemiebedingte kognitive Einbußen in Gedächtnisleistung signifikant über alterstypische Veränderungen in einem Zeitraum von zwei Jahren hinausgehen, während für verbale Funktion kein vergleichbarer Effekt nachweisbar ist. Höhere durchschnittliche Sommertemperaturen sind mit beschleunigten Einbußen in beiden kognitiven Bereichen assoziiert, während Maximaltemperaturen nicht mit kognitiven Veränderungen korrelieren. Auch wenn die sozialen und biologischen Wirkmechanismen hinter diesen Befunden noch zu ergründen sind, ist die gesellschaftspolitische Handlungsnotwendigkeit im Kontext multipler Krisen deutlich.
Keywords: 300; Cognitive health; Later life; Heat waves; Viral epidemic; Public health; Kognitive Gesundheit; Altern; Hitzewellen; Virus-Epidemie